Quantification of energy produced from an evacuated tube water heater in a real setting - Houri, Ahmad (2013)
For the first time, actual data regarding an evacuated tube SWH has been collected from an implemented system in Lebanon. The data collected was based on a number of sensors installed at various points in the system. The results indicated real hot water use of the household and operational temperatures throughout the year. The system provided more than 98% of the household needs indicating a clear over sizing of the system. Other findings include excessive heat generated in the summer, necessitating forced shadowing of the collectors. The system provided 3049 kWh/y and saved the family around $195. More significant savings are obtained by the electricity company since electricity in Lebanon is subsidized. This case study provides a reference point for the observed savings rather than estimated savings.